The philosophy of science and belief in God - Clark, Gordon H. 1902-1985 (University series: philosophical studies, 1964)
For the past two centuries Christianity has been subjected to an unrelenting barrage of criticism from scientists who have argued that many historical statements in the Bible are wrong; that man, and the universe as well, evolved-they were not created; that the Bible's view of the universe is primitive and mythological; and that the Christian view of God and man cannot be reconciled with our modem scientiﬁc discoveries. In the popular mind, the modern phrase, "it has been scientiﬁcally proved" has replaced the Biblical phrase "thus says the Lord," as the ﬁnal court of appeal. In The Philosophy of Science and Belief in God, Dr. Gordon H. Clark analyzes science from a Biblical and logical perspective. His conclusions are rather startling, perhaps not to scientists themselves, but to many laymen who have been deceived by the modern idolatry of science. Science, says Dr. Clark, can offer no objection to either God or the Bible, for science can never discover truth. It is ever learning but never able to come to the knowledge of truth. Dr. Gordon H. Clark was an eminent Christian philosopher and theologian, the author of 40 books, and the former Chairman of the Department of Philosophy at Butler University. He died in April 1985. Amazon.com.